Intertextuality in multi-layered texts of the Old Testament - Loader, James Alfred (Old Testament essays, 2008)
This article proceeds from the tenet that the Old Testament is, in various different ways, a layered text, to argue that the interpretation of the so-called 'final' text can only be done if the intertextual influence of the various pre-texts on the final text is taken into consideration. The different levels of intertextuality between a text and its pre-stages, its alternative forms (which are often also present in the 'final' form), and the context into which it was embedded are described. The complementarity of the synchronic and diachronic dimensions of a text and the importance of the intertextual network it forms with other texts are illustrated by two examples - that of the Succession Narrative (in which the parallels between Eli and David are shown to be hermeneutically significant), and the book of Esther (in which the parallels with Exodus are shown to be hermeneutically significant).